The Unemployment Invariant Hypothesis: Heterogeneous Panel Cointegration Evidence from U.S. State Level Data - Palamuleni, Mercy Laita (International Journal of Economics and Financial Issues, 2017)
We explore the long-run relationship between the unemployment rate and the labor force participation rates for United States over the period of 1976 to 2015. We use U.S. state level data and panel cointegration techniques that are robust to cross sectional heterogeneity, cross-sectional dependency, omitted variable bias and endogeniety issues. We find evidence that on average these two variables are cointegrated and are inversely related. Similar to studies that employ U.S. country level data, this study further questions the empirical relevance of the unemployment invariant hypothesis for the case of the United States. Keywords: Unemployment rate; Unemployment invariant hypothesis; panel cointegration JEL Classifications: E24, J60